Teacher Strategies in Cultivating Character Education: A Study of Religious, Honest, and Disciplined Values in Elementary School - Humairah, Dinda Annafia; Ulfah, Ulfah; Hariana, Kadek; Lagandesa, Yun Ratna; Fasli, Muhammad (Papanda Publisher, 2025)
Character education constitutes a fundamental aspect in forming students' moral integrity and personality. However, technological advancements and social changes present new challenges in instilling character values in elementary schools. This study aimed to analyze teacher strategies in cultivating character education values, specifically religious, honest, and disciplined values, among fourth-grade students at SDN Pombewe. Employing a qualitative approach with descriptive design, the research involved the school principal, classroom teachers, students, and parents as subjects. Data were collected through observation, interviews, and documentation, then analyzed using Miles and Huberman's interactive model encompassing data reduction, data display, and conclusion drawing. Findings revealed that teachers implemented four primary strategies: exemplary modeling, habituation, consistent rule enforcement, and reward provision. Religious values were instilled through collective prayer, worship instruction, and respectful behavior; honesty was developed through teacher modeling, honesty canteen activities, and anti-cheating policies; while discipline was formed through punctuality habits, rule compliance, and task responsibility. In conclusion, teacher strategies at SDN Pombewe proved effective in internalizing religious, honest, and disciplined values, simultaneously building a learning culture grounded in moral awareness, responsibility, and self-control